A 10-year experience of leiomyosarcoma of the inferior vena cava. (September 2022) - Pan, Jun; Qiu, Chen-yang; He, Yang-yan; Xue, Xing; Li, Dong-lin; Tian, Lu; Cheng, Fei; Wu, Zi-heng; Zhang, Hong-kun
Objectives: Leiomyosarcoma of the inferior vena cava (IVC) is rare. The study reviewed patients with IVC leiomyosarcoma in our hospital in the past ten years. Methods: Twenty patients diagnosed with IVC leiomyosarcoma between October 2010 and October 2020 were enrolled. Their clinical manifestations, treatments, and follow-up results were analyzed. Results: The sarcoma was located in the lower IVC segment in six patients, with 13 in the middle and one in the upper IVC segment. Eighteen patients underwent R0 resection. After resection, 16 patients (80%) had primary repair of the IVC, while four patients underwent ligation. During a mean follow-up of 37.7 months, seven patients died due to tumor metastasis, four patients were alive with the tumor recurrence and other nine patients were alive without recurrence. Conclusion: The management of the IVC after tumor resection depended on the tumor location and size. R0 resection provided a chance for long term survival.